SOSIOEKONOMI, PENGETAHUAN PENYAKIT DIARE DAN PENGETAHUAN SWAMEDIKASI DIARE PADA IBU BALITA DI YOGYAKARTA - Faridah Baroroh; Ana Hidayati; Siti Nurbayanti; Intan Tin Sari; Atikah Zain; Redy Redy; Siwi Retnaning Dyahayu (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
In Indonesia, the prevalence of diarrhea is highest among children under five. Economic factors and maternal knowledge are, in this case, significantly related to diarrhea incidence, and the latter substantially defines self-medication measures taken for acute diarrhea treatment. The research was intended to determine the extent to which socioeconomic conditions and diarrheal knowledge formed comprehension of such treatment. For this purpose, it employed a cross-sectional study with 504 research subjects, namely, mothers of children under five in the Special Region of Yogyakarta, Indonesia. Data were collected using a validated questionnaire consisting of items on socioeconomic details (education, employment, income), diarrheal knowledge, and relevant self-medication knowledge. Afterward, education and post-test were conducted using the same list of questions. Analytical techniques were carried out to identify how significant socioeconomic characteristics determined knowledge of diarrheal disease and self-medication.Results showed that, socioeconomically, a large proportion of research subjects attained secondary to tertiary education (76%), were unemployed (71%), and earned low income (62%). Educational attainment was found to be significantly related to levels of knowledge of diarrheal disease and self-medication (p < 0.005), but employment status and income were not (p > 0.005). Analysis results also indicate a significant relationship (p = 0.000) between the level of knowledge of diarrheal disease and that of diarrheal self-medication. Overall, socioeconomic status (i.e., level of education) and diarrheal knowledge is significantly related to diarrheal self-medication knowledge.